SPP1 Gene Polymorphisms Associated With Nephrolithiasis in Turkish Pediatric Patients - Tekin, Gökhan; Ertan, Pelin; Horasan, Gönül; Berdeli, Afig (Urology Journal, 2012)
PURPOSE: To investigate the association between SPP1 gene polymorphisms and nephrolithiasis. MATERIALS AND METHODS: A total of 65 pediatric patients and 50 healthy controls were enrolled in this study. Two known polymorphisms of the SPP1 gene, c.240T > C and c.708C > T nucleotide substitutions, both of which were also known as synonymous aminoacid polymorphisms, D80D and A236A, respectively, at SPP1 gene cDNA level were investigated. SPP1 gene polymorphism was evaluated using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism method. RESULTS: In c.240T > C polymorphism, C allele frequency [Odds Ratio (OR), 2.13; 95% Confidence Interval (CI), 1.170 to 3.880; P = .013] and CC genotype distribution (OR, 2.946; 95% CI, 0.832 to 10.431; P = .094) and in c.708C > T polymorphism, T allele frequency (OR, 2.183; 95% CI, 1.197 to 3.980; P = .011) and TT genotype distribution (OR, 3.056; 95% CI, 0.861 to 10.839; P = .084) were found to be higher in the patient group. CONCLUSION: SPP1 polymorphisms were found to be associated with nephrolithiasis and it may be suggested that SPP1 gene polymorphism could be a useful marker for evaluation of the early genetic risk factor in childhood nephrolithiasis.